The Effectiveness of Cognitive Behavioral Therapy With Mindfulness and an Internet Intervention for Obesity: A Case Series - Ogata, Keizaburo; Koyama, Ken I.; Amitani, Marie; Amitani, Haruka; Asakawa, Akihiro; Inui, Akio (Frontiers in Nutrition, 2018)
It is difficult for obese (body mass index of more than 30) and overweight (body mass index of 25–30) people to reduce and maintain their weight. The aim of this case series was to examine the effectiveness of a new cognitive behavioral therapy (CBT) program that combines mindfulness exercises (e.g., the raisin exercise and breathing exercises) and an online intervention to prevent dropout and subsequent weight gain in overweight participants. This case series included three participants, for whom previous weight reduction programs had been unsuccessful. All participants completed the program (60-minute, group sessions provided weekly for nine weeks) and an 18-month follow-up assessment. Results showed that all participants succeeded in losing weight (loss ranged from 5.30% to 8.88% of their total body weight). Although rebound weight gain is commonly observed in the first year following initial weight loss, the follow-up assessment showed that participants achieved further weight loss during the 18-month follow-up period. These results suggest that a CBT program that comprises mindfulness and an online intervention may be an effective method for weight loss and maintenance, and may prevent dropout in obese and overweight individuals. Trial Registration: This case series was registered at www.umin.ac.jp with identifier UMIN000029664.